The Political Responsiveness of Violent Crime Prosecution. (December 2018) - Boldt, Ethan D.; Boyd, Christina L.
Is a federal prosecutor's decision whether to pursue violent crime charges political? While prosecutors frequently assert their decision-making independence, their selection and operational constraints suggest a very different story. We assess whether political factors related to the prosecution priorities of the president, Congress, and the local public affect federal prosecutors' decisions to pursue or decline charges in violent crime matters. To empirically examine this, we utilize data from 89 U.S. Attorneys offices from 1996 to 2011. The results provide rich new insight into when and why federal prosecutors' decisions to pursue or decline prosecutions are driven by the preferences of the president, Congress, and the local public. The findings also have important broader implications for the role of political factors in a U.S. criminal justice system believed by many to be in crisis.